Actualisation and Productivity in Strengthening Productive Moral Intelligence at the Madrasah Pendidikan Asas Daru Ashomiddin Service's (PADA) Singapore - Nola Fibriyani Bte Salman (Jurnal Educative: Journal of Educational Studies, 2022)
Singaporeans are ethnically diverse with Chinese, Malay, Indian, Caucasians population. Forty-two percent of Singaporeans are foreigners working or studying there. Fifty percent of workers are from foreign countries. With such a background, Singapore faces various problems for its children, including moral problems. This research uses a qualitative field approach. Researcher recorded learning activities at the Madrasah Pendidikan Asas Daru Ashomiddin Service's (PADA) Singapore. The data was then descriptively and qualitatively analyzed. The findings of this study indicate that strengthening moral education intelligence and its relationship with philosophy and psychology can produce  a capable generation for today's global era. Strengthening Islamic moral intelligence that is integrated with the philosophy of science is a solution to the moral issues that Singoperean society now face.